Initiation and development of a mesoscale convective system in the Ebro River Valley and related heavy precipitation over northeastern Spain during HyMeX IOP 15a. (31st January 2017) - Lee, K.‐O.; Flamant, C.; Ducrocq, V.; Duffourg, F.; Fourrié, N.; Delanoë, J.; Bech, J.
Abstract : During Intensive Observation Period 15a (20 October 2012) of the first Special Observation Period of the Hydrological cycle in the Mediterranean Experiment, northeastern Spain experienced heavy precipitation (130 mm in 24 h) associated with a retrograde regeneration mesoscale convective system (MCS) developing in the exit region of the Ebro River Valley (ERV). The life cycle of the MCS that brought intense hourly rainfall (34 mm) from the foothills of the Iberian Plateau to the central Pyrenees, as well as the detailed structure of the moist marine flow upstream, were analysed using a combination of ground‐based, airborne and space‐borne observations as well as model analyses. Over the Balearic Sea, the southwesterlies along the northeastern flank of a surface low converged with southeasterlies from North Africa, creating a near‐surface moisture tongue in the region of the Balearic Islands, and a southeast–northwest oriented convergence line within a cloud cluster advecting from northern Africa. Airborne lidar measurements, acquired upstream of the ERV, evidenced water vapour mixing ratios in excess of 15 g kg −1 in the marine atmospheric boundary layer. In the mid‐level (700 hPa), the presence of an elevated moisture plume from tropical Africa contributed about one third to the large moisture content present over the western Mediterranean Sea. In this moist environment, the MCS was initiated over the orography of the northeastern tip of the Iberian plateau, due to the combined influence of the approaching convergence line ahead of the surface low and the convergence resulting from weak northwesterlies channelled in the ERV and the easterlies impinging on the coastal range. After the initiation phase, the MCS further developed over the foothills of the Iberian Plateau and moved into the ERV and along the southern flank of the Pyrenees, thanks to the penetration of the warm and moist maritime southeasterly flow through the narrow gap between the northeastern part of the Iberian Plateau and the Catalan coastal range.